KOMPOSISI DAN POLA SEBARAN POLYCHAETA DI PESISIR MANGKANG KULON KECAMATAN TUGU, SEMARANG BERDASARKAN TATA GUNA LAHAN - Syarif Prasetyo; Sapto punomo Putro; Riche Hariyati (Jurnal Akademika Biologi, 2012)
Polychaeta is a biota that became one component of the food chain in the ocean. Having different tolerances, so it is often used as an indicator of changes in water quality. This study examines the composition of polychaeta which includes abundance, dominance, diversity, evennes, and its distribution patterns at two different locations, ie mangrove vegetation and fish farming areas. Location was chosen by looking the land use’s differences in the coastal area of Mangkang Kulon Tugu Subistrict Semarang. Sampling was conducted in July and August 2012. Analysis of physico-chemical parameters to the water samples and the substrate did directly in the field and laboratory. Samples of polychaeta were obtained by a 1 mm benthic sieve. Identifications are made to genus level. Then, calculating the number of genus, abundance, dominance, evennes, diversity and distribution patterns in each station. Overall, there are 15 genus come from polychaeta, they are Capitellidea, Nereididae,  Spionidae, Dorvillidae, Lumbrineridae, Cirratulidae, Oenoidae and Sabellidae. The average of polychaeta abundance index is in the above of 500 ind/m2. Diversity index (H') is relatively sufficient (1,332-2,073). Evennes index value (E) is high (>0,6) and there is no dominat genus with dominant index (D) low (<0.5). The distribution pattern is the same (Id: <1). The Differences sampling location affect on the composition and distribution patterns of the Polychaeta and physico-chemical factors. While sampling time does not affect the composition and distribution patterns of polychaeta and physico-chemical factors waters. Capitellidae is an opportunistic polychaeta that is more common in fish farming areas (70-81%) than in the mangorove vegetation areas (59 -72%). Keywords: Polychaeta, Mangkang Kulon, mangrove, fish farming, composition, distribution pattern,